A study on municipal solid waste management in Sarawak - Clement Jeremy ak, Joseph Julian. (Universiti Malaysia Sarawak, UNIMAS, 2004)
Waste has become the main by - products of everyday living in Sarawak. Waste generation and composition are strongly related to the regional socio - economic conditions and also the amount of population in every district in Sarawak. Socio - economic f actors that enable an increase in the standards of living of the regional economy will influence the per capita rate of waste generation and the composition of waste generated. The per capita waste generation may generally increase concurrently with increa sed standards of living. According to a Natural Resources and Environmental Board (NREB) research, the total amount of solid waste generated that a single person generated a day is estimated an average of 0.67 kg of waste a day in Sarawak. Kuching is the m ost densely populated district in Sarawak and estimated to grow at a steady rate approximately 2% per year. Municipal Solid Waste management in Kuching District is primarily the responsibility of the local authorities (LA). Dewan Bandaraya Kuching Utara (D BKU), Majlis Bandaraya Kuching Sealatan (MBKS) and Majlis Perbandaran Padawan (MPP) responsible in the study of solid waste for their administrative area while Trienekens Sdn. Bhd is the private sector that responsible for disposing, studying and collectin g solid waste in Kuching. Results from the increase volume of solid waste in Kuching, the local authorities have conducted a sanitary landfill system as a solid waste disposal.The legal facility that is available for disposal of solid waste within the Kuch ing city boundaries is the Matang dump site and Kuching Integrated Waste Management Park at Mambong. From the data acquisition, an alternative design of sanitary landfill will be produced. All the data are collected from Trienekens Sdn. Bhd, DBKU, MBKS, MP P, NREB and DOS. The data required for alternative design of a sanitary landfill are population of people in Kuching, propose design life of a landfill, total municipal solid waste generated in Kuching and amount of municipal solid waste generated by a sin gle person per day.